Whole-of-government approaches to fragile states and situations - Finn Stepputat; Lauren Greenwood (Danish Institute for International Studies (DIIS), 2013)
Since national security interests have played a role in donor's engagement in fragile states and situations, development actors have seen new political and security actors entering these theatres. Hence, development actors and practices have been subjected to new pressures, not least to the expectations for rapid results that accompany the heightened political profile of these donor engagements. As the case of Afghanistan has demonstrated, such pressures multiplied once donor governments had 'boots on the ground'. On this background, the ambition of this report is to take stock of evaluations of WoGAs in order to answer: 1) if national WoG approaches work according to their objectives of improving joined-up governmental responses to state fragility and conflict; and 2) if it is possible to identify how WoGAs influence the outcomes of international interventions in areas of fragile statehood. The report describes the evolving approaches of the UK, the Netherlands and Denmark, and has identified evaluations and reports that deal with these donors' activities in Afghanistan, Somalia, (Southern) Sudan, DRC, Burundi and Sierra Leone.
Keywords: 300